Características químicas de um Gleissolo sob diferentes sistemas de uso, nas margens do rio Guamá, Belém, Pará - Lopes, Elessandra Laura da Nogueira; Fernandes, Antônio Rodrigues; Grimaldi, Catherine; Ruivo, Maria de Lourdes Pinheiro; Rodrigues, Tarcísio Ewerton; Sarrazin, Max (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
The effect of the use of the soil on the fertility has been studied, in Gleyssoil under three different management systems. Collections had been made before the rainy period in the following handling systems: rice (Oriza sativa L.) plantation area, cultivated for approximately 40 years, with some interruptions in during this period. Some times the culture was mechanized, with use of plowshare and harrow; pasture area with plantation of canarana (Echinochloa pyramidalis Hitch.), cultivated for 20 years, without the use of fertilizers; and lowland area with natural vegetation. The samples of soil were collected in ten points, set by using the transect methodology, to four depths 0-10, 10-20, 20-30 and 30-40 cm in each point. The results demonstrate that the soil under natural conditions, presented chemical characteristics which insure to the soil a high potential for the agricultural use. The agricultural culture of the lowland soil in the Guamá River provoked a reduction in the concentration of P and K. The soil usage system with pasture presented better sustainability on it fertility than the system with rice cultivation, beyond the improvement of the chemical characteristics and raise in the organic matter concentration, when related to the natural vegetation system.